Negative ecstasies : Georges Bataille and the study of religion - Biles, Jeremy; Brintnall, Kent (Perspectives in continental philosophy., 2015)
Negative Ecstasies discusses the contribution and significance of the work of Georges Bataille to the contemporary study of religion and theology, collecting essays that examine specific case studies and make connections to other significant scholars in the field.